Opieka ginekologiczna z perspektywy pacjentek ze szczególnym uwzględnieniem osób w wieku 12-25 lat, LBTQ oraz z niepełnosprawnościami - Wonatowska, Patrycja; Skonieczna, Joanna (Journal of Education, Health and Sport, 2015)
Wonatowska Patrycja, Skonieczna Joanna. Opieka ginekologiczna z perspektywy pacjentek ze szczególnym uwzględnieniem osób w wieku 12-25 lat, LBTQ oraz z niepełnosprawnościami = Gynecological care from the perspective of patients with special focus on patients aged 12-25 years, LBTQ and with disabilities. Journal of Education, Health and Sport. 2015;5(8):343-352. ISSN 2391-8306. DOI10.5281/zenodo.29170 http://dx.doi.org/10.5281/zenodo.29170 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A343-352 https://pbn.nauka.gov.pl/works/612123 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-ca1a826b-2888-486c-b598-007eab8b6672 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.08.2015. Revised 24.08.2015. Accepted: 24.08.2015. Opieka ginekologiczna z perspektywy pacjentek ze szczególnym uwzględnieniem osób w wieku 12-25 lat, LBTQ oraz z niepełnosprawnościami Gynecological care from the perspective of patients with special focus on patients aged 12-25 years, LBTQ and with disabilities Wonatowska Patrycja (1), Skonieczna Joanna (2) (1) Grupa Edukatorów Seksualnych “Ponton”, Federacja na rzecz Kobiet i Planowania Rodziny (2) Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny (1) Group of Sex Educators “Ponton”, Federation for Women and Family Planning (2) Public Health Department, Medical University of Warsaw Słowa kluczowe: promocja zdrowia, ginekologia, młodzież, osoby niepełnosprawne. Key words: health promotion, gynecology, adolescence, people with disabilities. Streszczenie Wprowadzenie i cel pracy: Zdrowie reprodukcyjne i seksualne to stan całkowitego fizycznego, psychicznego i społecznego dobrego samopoczucia. Celem pracy była ocena stanu opieki ginekologicznej z perspektywy osób z niej korzystających, ze szczególnym uwzględnieniem osób w wieku od 12. do 25. roku życia, osób LBTQ oraz osób z niepełnosprawnościami. Materiał i metoda: Wykorzystanym narzędziem był autorski kwestionariusz wypełniany anonimowo w trybie online. Badaniem objęto 2501 respondentek. Wyniki: Największą grupę, która wypełniła ankietę, stanowiły osoby w wieku 21-30 lat (62%). Blisko 18% to osoby nieheteroseksualne, a prawie 8% to osoby z niepełnosprawnościami. Najczęstszym powodem pójścia na wizytę do ginekologa była troska o własne zdrowie (38,7%). Prawie 15% traktuje wizytę jako „zło konieczne”, a u 9,7% budzi ona skrępowanie. Na wybór lekarza zdecydowanie największy wpływ ma opinia znajomych osób (67,2%). Najważniejszym oczekiwaniem podczas wizyty jest, aby lekarz wyczerpująco odpowiadał na pytania (80,4%). Pacjentki z niepełnosprawnościami ruchowymi zwracały uwagę na brak udogodnień lub bariery architektoniczne. Wnioski: Brakuje u kobiet wykształconego od najmłodszych lat poczucia odpowiedzialności za własne zdrowie reprodukcyjne i seksualne, które przekładałoby się na potrzebę regularnego odbywania wizyt ginekologicznych. Za wykształcenie odpowiednich nawyków prozdrowotnych powinni być odpowiedzialni rodzice młodych kobiet oraz szkolna edukacja seksualna. W toku edukacji ginekologów należy położyć większy nacisk na umiejętności właściwego podejścia do pacjentki jako osoby, w tym odpowiedniego sposobu komunikowania się i przekazywania rzetelnej wiedzy. Ginekolog powinien stanowić główne źródło informacji kobiety nt. jej zdrowia reprodukcyjnego i seksualnego. Abstract Introduction: Reproductive health is defined as a state of physical, mental, and social well-being in all matters relating to the reproductive system, at all stages of life. The aim of this research was to evaluate gynecological care from the perspective of people using it, especially people between 12 to 25 years old, LBTQ and people with disabilities. Material and Methods: The study covered 2501 respondents. Author's questionnaire was available on-line. Results: Most questionnaires were filled by people aged 21-30 years (62%). Nearly 18% belonged to the LBTQ group, and almost 8% were people with disabilities. The most common reason to have a gynecological visit was a concern for their own health (38,7%). Almost 15% treated visits as a „necessary evil” and in 9,7% of responders feel ashamed. The biggest impact on choosing a doctor have the opinions of friends and close people (67,2%). During the visit the most important is that the doctor fully answers all questions (80,4%). There are significant barriers to access to gynecological care, especially for those women who have serious mobility problems. Conclusions: There is a necessity to increase a sense of responsibility among women from an early age for their own sexual and reproductive health which would alter into the regular gynecological care. Parents and school sex education should take part into creation of appropriate healthy habits of young women. Future gynecologist should be educated how important are skills of suitable approach to the patient including appropriate method of communication and sharing of reliable knowledge. The gynecologist should be the main source of information about reproductive and sexual health among women.